2018
DOI: 10.3390/ijms19010318
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and Aging: The Role of the TREM2–DAP12 and CX3CL1-CX3CR1 Axes

Abstract: Depending on the species, microglial cells represent 5–20% of glial cells in the adult brain. As the innate immune effector of the brain, microglia are involved in several functions: regulation of inflammation, synaptic connectivity, programmed cell death, wiring and circuitry formation, phagocytosis of cell debris, and synaptic pruning and sculpting of postnatal neural circuits. Moreover, microglia contribute to some neurodevelopmental disorders such as Nasu-Hakola disease (NHD), and to aged-associated neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(146 citation statements)
references
References 181 publications
(232 reference statements)
2
138
0
Order By: Relevance
“…As such differential expression or manipulation of Trem2 may lead to microglial and monocyte regulatory disarray, and likely leads to differing local, temporal, and end state outcomes with increasing age and disease progression (66). TREM2 and CX3CR1 signalling both decline in aged microglia, leading to an accumulation of dystrophic and pro-inflammatory microglia in ageing (72). We have previously shown that ageing compounds gene expression changes and disease outcome in retinal ganglion cells (34), and so these gene expression changes in myeloid derived cells should be considered in the context of increasing age in addition to disease.…”
Section: Discussionmentioning
confidence: 99%
“…As such differential expression or manipulation of Trem2 may lead to microglial and monocyte regulatory disarray, and likely leads to differing local, temporal, and end state outcomes with increasing age and disease progression (66). TREM2 and CX3CR1 signalling both decline in aged microglia, leading to an accumulation of dystrophic and pro-inflammatory microglia in ageing (72). We have previously shown that ageing compounds gene expression changes and disease outcome in retinal ganglion cells (34), and so these gene expression changes in myeloid derived cells should be considered in the context of increasing age in addition to disease.…”
Section: Discussionmentioning
confidence: 99%
“…In order to perform these above‐mentioned functions a diverse array of receptors including TAM receptors, glutamate receptors, and purinergic receptors are used by microglia to efficiently communicate with other cells (Fourgeaud et al, ; York, Bernier, & MacVicar, ). Among these complex systems the CX3CL1/CX3CR1 and CD200‐CD200R axes play key roles in microglia–neuron contact (Eyo & Wu, ; Kierdorf & Prinz, ; Limatola & Ransohoff, ; Mecca, Giambanco, Donato, & Arcuri, ). Indeed, the CX3CR1 −/− mouse exhibited profound alterations in both morphology and connectivity of the mature newborn hippocampal granule neurons (Bolos et al, ).…”
Section: Multi‐tasking Microglia: a Friend For Brain Homeostasismentioning
confidence: 99%
“…Among these genes, polymorphisms in CX3CR1 influence disease progression but not risk in Alzheimer's disease as well as in amyotrophic lateral sclerosis, two diseases characterized by neuroinflammation (Lopez-Lopez, Gamez et al, 2014, Lopez-Lopez, Gelpi et al, 2017. CX3CR1 is the receptor for the chemokine fractalkine (CX3CL1) and is a critical signaling pathway for microglia-neuron crosstalk (Lauro, Catalano et al, 2015, Mecca, Giambanco et al, 2018. Interestingly, the CX3CL1/CX3CR1 axis is implicated in the regulation of cognitive functions and synaptic plasticity, particularly in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%